Apollo in Perspective : Spaceflight Then and Now - Allday, Jonathan (Boca Raton, FL : CRC Press, 2020)
This special edition of Apollo in Perspective marks the 50th anniversary of the Apollo 11 Moon landing in 1969. Updated and revised throughout, it takes a retrospective look at the Apollo space program and the technology that was used to land a man on the Moon. In addition, there is a new chapter looking forward to the future of contemporary spaceflight in returning to the Moon (project Artemis) and going on to Mars. Using simple illustrations and school-level mathematics, it explains the basic physics and technology of spaceflight, from how rockets work to the dynamics of orbits and how to simulate gravity in a rotating spacecraft. A mathematical appendix shows how some of the formulas can be derived. This is an excellent introduction to astronautics for anyone interested in space and spaceflight. Features: Accessible, written in a friendly and informal style Contains real-world examples Updated throughout, with new chapters on the Apollo missions and the immediate future of human spaceflight From the Foreword "I am sure there is a woman or a man alive today who will land on the Moon and on Mars. This book will certainly help them be ready for such a journey. Most importantly, it explains not only what happened 50 years ago, but how the Apollo missions happened, and the science that is required to do it again, or to go further, to Mars. If the reader is younger, still in school and perhaps considering the sciences, this book will introduce ideas that will help you choose the subjects to study which can help you to make your space travel a reality. For others, the book will be an exciting and thought provoking read that gives a vision of the near future in space, which all of us on planet Earth will be able to enjoy as the adventure unfolds." -- Michael Foale, CBE, former-NASA astronaut
OCLC-licensed vendor bibliographic record.
Keywords: Project Apollo (U.S.); Space flight; SCIENCE / Astrophysics & Space Science; SCIENCE / Physics; TECHNOLOGY / Engineering / Mechanical